Prevalence and severity of anemia among pregnant women in primary health centers/Erbil City - Abdulwahid, Rushna Ghazi; Ahmed, Hamdia Mirkhan (Kurdistan Journal of Applied Research, 2017)
Anemia in pregnancy is a major public health problem, especially in developing countries. Nutritional anemia is the most common type of anemia worldwide and mainly includes iron, folic acid, vitamin B12 and vitamin C deficiencies. Iron deficiency contributes to half of the burden of anemia globally. The objectives of this study were to find out the prevalence and severity of anemia among pregnant women. A descriptive study was conducted on 600 pregnant women, during the period October 2015 to November 2016 at four primary health care centers in Erbil city. Data gathered through interview with study sample and filling questionnaire format and reviewing their antenatal records. Blood hemoglobin level was measured to assess the severity of anemia. Chi-square test and regression were used to analyze the data. Prevalence of anemia was 46.2%, and 67.1% of the anemic women had mild anemia. There was a significant association of severity of anemia with wife education and occupation, smoking, the number of abortions and cesarean section, ante partum hemorrhage, taking tablets of iron and folic acid per month. The study concluded that prevalence of anemia considered high in Erbil city, the highest percentage had mild anemia.